Analysis on capability of harmonic damping using active filter acting as resistive harmonic impedance - Hasan, K.N.Md. (2013)
This paper presents the analysis of shunt active filter (SAF) in harmonic damping. SAF with voltage-based detection control act as an active damping and able to attenuate harmonic propagation throughout the power distribution network. The active filter is implemented on two different power line networks to assess its practicality in different network configuration. The first network is 220-V distribution power line and the second network is the reduced equivalent WPP network of 150-kV, 444.4-MVA. Assessment on the best place for active filter implementation is supported by using harmonic resonance mode analysis method. Â© 2013 IEEE.